Regional Authority, Transnational Lobbying and the Allocation of Structural Funds in the European Union - Chalmers, Adam William (Journal of common market studies, 2013)
The allocation of European Union (EU) structural funds is subject to fierce regional lobbying. This article examines the extent to which regions with greater political authority are better able to lobby for funds than their weaker counterparts. Existing research acknowledging the importance of regional authority in these processes has used inadequate indicators. This analysis, drawing on the Regional Authority Index, is the first to use regional‐level data disaggregating between regional authority as self‐rule and shared‐rule. It also uses data that measure the lobbying capacity of regions' Brussels‐based lobbying offices. Controlling for a battery of competing and control variables, Tobit regression analyses of 181 regions receiving funds in the 2007–13 period suggest that regional authority expressed as shared‐rule, but not self‐rule, has a significant impact on the allocation of structural funds in the EU.